2014
DOI: 10.4236/ce.2014.521207
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Perceptions of Their Learning Environment, Well-Being and Academic Self-Concept

Abstract: This study investigated medical students' perceptions of their learning environment and how these related to well-being in terms of experienced exhaustion and losing interest in personal studies. The goal was to also examine whether students' perceptions and experiences of well-being related to their academic self-concept. Experiences were compared between lecture-based learning (LBL) and problem-based learning (PBL) environments. The MED NORD questionnaire was used to measure students' experiences of their le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
5
14
0
1
Order By: Relevance
“…Students who perceive the workload as high in their learning environment are more likely to display a lack of interest in their studies as well as exhaustion. This is particularly true for beginning PBL students (Litmanen et al 2014). Another factor that can lead to more surface learning is the assessment methods used.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Students who perceive the workload as high in their learning environment are more likely to display a lack of interest in their studies as well as exhaustion. This is particularly true for beginning PBL students (Litmanen et al 2014). Another factor that can lead to more surface learning is the assessment methods used.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Similar dysfunctional orientation was identified by Lonka et al (2008) using a variable-centered approach, and Heikkilä et al (2012) using a person-oriented approach. However, it is quite typical for exhaustion, increased workload, and lack of self-regulation to be experienced among freshmen (Lindblom-Ylänne & Lonka, 2000;Litmanen, et al, 2014). Many of these students are coming directly from high school and still 'learning how to learn' in the academic community.…”
Section: Discussionmentioning
confidence: 99%
“…However, even well-motivated and highly selected students may face problems in regulating their learning (Donche, Coertjens, & van Petegem, 2010;Donche & van Petegem, 2009;Heikkilä, Lonka, Nieminen, & Niemivirta, 2012;Heikkilä, Niemivirta, Nieminen, & Lonka, 2011;Nieminen, Lindblom-Ylänne, & Lonka, 2004). Problems in self-regulation may further increase the risk of exhaustion (Litmanen, Loyens, Sjöblom, & Lonka, 2014;Misra, McKean, West, & Russo, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It tested the construct validity by CFA. The study revealed that the hypothesized model had an acceptable fit with the sample data [45]. Another example is a study conducted in Finland at the University of Helsinki, Faculty of Education where other scales were examined for construct validity.…”
Section: Discussionmentioning
confidence: 89%
“…It is worth-mentioning that this is the first study that measured the internal structure of MED-NORD questionnaire using CFA with different scales and items under different scales. However, other studies have used limited variants of MED-NORD questionnaire [45,46].…”
Section: Discussionmentioning
confidence: 99%